Characterization of adsorption of humic acid onto alumina using quartz crystal microbalance with dissipation - Yan, Mingquan (Langmuir : the ACS journal of surfaces and colloids, 2011)
In this paper, a quartz crystal microbalance with dissipation monitoring (QCM-D) is used to investigate humic acid (HA) adsorption onto alumina (Al(2)O(3)). The amount of adsorption and layer structures of HA were determined by the real-time monitoring of resonance frequency and energy dissipation changes (Δf and ΔD). The effect of HA concentration, HA molecular characteristics (molecular weight and polarity), and pH on HA adsorption onto Al(2)O(3) were investigated. The mass of HA adsorption increases as the concentration of HA increases. The masses are about 24, 60, and 87 ng cm(-2) as the concentration of DOC is 1.0, 4.85, and 92.0 mg L(-1), respectively. The adsorbed layer of HA is more nonrigid, and the mass of HA adsorption is higher at weakly acidic pH values. It was 20, 80, 65, and 45 ng cm(-2) at pH values of 4.5, 5.5, 6.5, and 8.0, respectively. This reveals that efficient HA removal by coagulation at weakly acidic pH values is not just due to the hydrolysis of Al ions as previously presumed. The adsorbed layer of hydrophobic HA is more nonrigid than hydrophobic HA (fractionated by Amberlite XAD-8 resin), and the mass adsorption for the hydrophobic fraction is about four times higher than the hydrophilic fraction (120 ng cm(-2) and 30 ng cm(-2)). The method is of value in the research to establish a quantified calculation model for the coagulation process